Valosin-containing protein (VCP): structure, functions, and implications in neurodegenerative diseases. Issue 6 (1st November 2016) - Yeo, Bo Kyoung; Yu, Seong-Woon
ABSTRACT: Valosin-containing protein (VCP) is a hexameric protein belonging to the type II AAA+ (A TPasesA ssociated with diverse cellularA ctivities) protein family. VCP governs multiple cellular processes and its diverse functions are determined by its interaction with a wide variety of partners and cofactors. Recently, mutations in VCP were suggested to cause inclusion body myopathy associated with Paget disease of bone and frontotemporal dementia, amyotrophic lateral sclerosis, and Huntington's disease. However, the pathogenic mechanisms of VCP mutations in these diseases are still largely unknown. In this review, we summarize the structure and cellular functions of VCP, especially focusing on apoptosis and two major cellular degradation pathways, the ubiquitin–proteasome system and autophagy. We also list the representative VCP mutations and discuss their potential association with neurodegenerative diseases.